In-plane strengthening of masonry buildings with timber panels. Issue 5 (1st May 2021) - Pozza, Luca; Marchi, Luca; Trutalli, Davide; Scotta, Roberto
Abstract : The in-plane strengthening of masonry walls plays a key role in the improvement of the global seismic behaviour of masonry buildings. Various strengthening techniques are currently available, such as coatings, confinement or injection and the use of cement-based materials or steel- or fibre-reinforced polymers or mortars. In this work, two innovative strengthening techniques for existing masonry buildings were investigated: the use of glued or nailed timber wall panels connected to the outer and/or inner face of the masonry wall. Their effectiveness in reducing the seismic vulnerability of existing masonry walls was assessed in tests and numerical simulations. The test results demonstrated improvements in strength, rocking displacement capacity and energy dissipation capacity. The numerical analyses, conducted with non-linear models calibrated on experimental results available in the literature, confirmed the advantages of these interventions, comparing the effects of using monolithic or coupled glued or nailed wall panels, provided that particular attention is given to their connection to the existing structure.